2015
DOI: 10.25260/ea.15.25.1.0.54
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la ardilla de vientre rojo sobre la comunidad de aves en la Región Pampeana, Argentina

Abstract: RESUMEN.Las invasiones biológicas son una amenaza para las especies nativas. La ardilla de vientre rojo Callosciurus erythraeus fue introducida en Luján (provincia de Buenos Aires, Argentina) en 1970, donde estableció la principal población silvestre del país. Las ardillas podrían afectar a las aves a través de la depredación de nidadas, de la competencia por alimento y sitios para nidificar, o por interferencia. El objetivo fue comparar la composición, densidad y riqueza de especies de aves en sitios arbolado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other native wildlife that could be affected by the presence of the Callosciurus squirrels is the bird community. In Argentina, Pallas's squirrels affect the bird species richness, suggesting a species-specific response of the avian community in an area where native arboreal diurnal mammals are not present [113]. Pallas's squirrels did not systematically consume bird eggs (see, also, Reference [114] in Argentina and [115] in Japan), but Messetta et al [113] suggested that squirrels might interfere with birds that modify their behavior, affect reproductive success or compete for food and nesting sites.…”
Section: Harm To Native Speciesmentioning
confidence: 99%
“…Other native wildlife that could be affected by the presence of the Callosciurus squirrels is the bird community. In Argentina, Pallas's squirrels affect the bird species richness, suggesting a species-specific response of the avian community in an area where native arboreal diurnal mammals are not present [113]. Pallas's squirrels did not systematically consume bird eggs (see, also, Reference [114] in Argentina and [115] in Japan), but Messetta et al [113] suggested that squirrels might interfere with birds that modify their behavior, affect reproductive success or compete for food and nesting sites.…”
Section: Harm To Native Speciesmentioning
confidence: 99%
“…Unfortunately, competitive interactions of C. erythraeus in Argentina have not been studied yet although resource use overlap could be high with D. albiventris (Chemisquy and Martin 2019; Guicho ´n et al 2019; personal observation). Also, other taxa deserve attention as potential competitors, such as some bird species (Messetta et al 2015). Further studies monitoring new interactions through time and space (e.g.…”
Section: Tablementioning
confidence: 99%